CONTROVERSIAL ASPECTS REGARDING TAX EVASION - Mircea-Constantin SINESCU; Adrian-Lucian CATRINOIU (Challenges of the Knowledge Society)
Throughout the paper, we have highlighted some controversial aspects regarding the crime of tax evasion, referring to some important decisions of the High Court of Cassation and Justice and also of the Bucharest Court of Appeal. Debating upon the impunity provision stated by art. 10 of Law no. 241/2005, the study also sheds light upon the issue of the perspective of the judicial organs regarding the juridical regime of the tax due for dividends. The main focus of the paper leads to the situations when there is legal ground for the tax due for dividends to be considered part of the damage caused by tax evasion crime. The study includes a short analysis of some relevant provisions of the Romanian Fiscal Code and also some aspects deriving from decisions issued by the Administrative and Tax Litigation Chamber of The High Court of Cassation and Justice concerning the legal regime of dividends. Consequently, the authors are presenting both perspectives of the interpretation of the issue regarding the tax due for dividends to be considered part of the damage caused by tax evasion crime, resulting from two decisions of the two Criminal Sections of The Bucharest Court of Appeal, also arguing in favour of the most solid interpretation among them